Update on the Cognitive Presentations of iNPH for Clinicians - Langheinrich, Tobias; Chen, Cliff; Thomas, Owen (Frontiers in Neurology, 2022)
This mini-review focuses on cognitive impairment in iNPH. It is one of the characteristic triad of symptoms in a condition long considered to be the only treatable dementia. We present an update on recent developments in clinical, neuropsychological, neuroimaging and biomarker aspects. Significant advances in our understanding have been made, notably regarding biomarkers, but iNPH remains a difficult diagnosis. Stronger evidence for permanent surgical treatment is emerging but selection for treatment remains challenging, in particular with regards to cognitive presentations. Encouragingly, there has been increasing interest in iNPH, but more research is required to better define the underlying pathology and delineate it from other conditions that overlap with it, in order to inform best practice for the clinician managing the cognitively impaired patient. In the meantime, we strongly encourage a multidisciplinary approach and a structured service pathway to maximise patient benefit.